2014
DOI: 10.1002/mc.22199
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of colon tumors induced by a dietary carcinogen PhIP in CYP1A humanized mice: Identification of mutation of β‐catenin/Ctnnb1 as the driver gene for the carcinogenesis

Abstract: Replacing mouse Cyp1a with human CYP1A enables the humanized CYP1A mice to mimics human metabolism of the dietary carcinogen, 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP), by N2-hydroxylation to a proximate carcinogen. Our previous study demonstrated that PhIP, in combined with the dextrin sulfate sodium (DSS)-induced colitis, induces colon carcinogenesis in hCYP1A mice. Here, we employed whole exome sequencing and found multiple gene mutations in PhIP/DSS-induced colon tumors. Mutations in the exon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 63 publications
2
26
1
Order By: Relevance
“…These frequencies are consistent with previous studies for Caucasian EBDC (17.5-75%) (16,36,37) and GBC (46.2-63%) (15,36,38). Additionally, the frequencies of KRAS mutations in Japanese EBDC (27.2%) and GBC (14.3%) are in agreement with previous studies (16,19,20,36,37).…”
Section: Discussionsupporting
confidence: 92%
“…These frequencies are consistent with previous studies for Caucasian EBDC (17.5-75%) (16,36,37) and GBC (46.2-63%) (15,36,38). Additionally, the frequencies of KRAS mutations in Japanese EBDC (27.2%) and GBC (14.3%) are in agreement with previous studies (16,19,20,36,37).…”
Section: Discussionsupporting
confidence: 92%
“…These treatment changes not only improved the health of the mice considerably, but also increased colon tumor incidence to 100% (from previous ∼86%) and multiplicity to ∼6 tumors per mouse (from previous ∼4 tumors). The increased tumor incidence in mice may be attributed to longer exposure to the PhIP carcinogen, which leads to greater likelihood of cells acquiring key mutations that drive the PhIP/DSS colon carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis for Ctnnb1/b-catenin mutation hot spots was performed using Sanger sequencing method as described previously in Wang et al (2015). Ctnnb1/b-catenin exon 3 was directly amplified from extracted DNAs using by Advantage 2 PCR kit (Clontech Laboratories, Inc, Mountain View, California) and primers, CTAACATACTCTGTTTTTACAGCTGAC and CAGCTACTTGCTCTT GCGTGA (250bp product size).…”
Section: Methodsmentioning
confidence: 99%
“…Previous study in our lab showed a majority of PhIP/DSS-induce colon tumors carried dominant active mutations of the Ctnnb1/ b-catenin gene, chiefly in codon 32 and 34 of exon 3 (Wang et al, 2015). To determine whether these mutations can be detected in earlier preneoplastic colon, laser capture microdissection and targeted sequencing were employed.…”
Section: Dominant Active Ctnnb1/b-catenin Mutations In the High-gradementioning
confidence: 99%
See 1 more Smart Citation